Forms of Water Loss and Water Requirement of Rice in Kole Lands - Lissy Devid Chirayath (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 1988)
Rice is the most important and extensively cultivated food crop in Kerala. Efficient use of water for crop production has been a major concern for centuries. As the water needs of rice is many times greater than other crops, a precise knowledge of water requirement of crop attains importance for increasing production. The present investigation was taken up to estimate the losses through evaporation, transpiration, percolation and to assess the total water requirement of a medium duration rice variety Jaya, in Punja season in Kanjany Kole lands in Trichur district, which has not been assessed so far. The Kole areas are reclaimed lake beds below mean sea level. The main source of irrigation water to the Kole lands is from the Peechi irrigations system. The experiment was conducted during Punja season of 1986 in Kanjany Kole lands. Estimations of evaporation, transpiration and percolation were made on the basis of measurements, using evaporimeter, evapotranspirimeter and field hook gauge. From the study it was revealed that the total water requirement was 2134.22 mm. Percentages of water lost by percolation, transpiration and evaporation were 70.34, 17.32 and 12.34 respectively. Rate of evaporation was almost constant during first twenty days, then started decreasing up to 69 days and then onwards was almost constant during the final stage. Rate of transpiration remained almost constant up to ten days, then started increasing up to fifty days and then remained almost a constant up to final stage. Rate of total loss of water was increasing from transplanting, reached a maximum of 28.6 mm after 26 days, then started decreasing up to final stage. When the level of water in the canal is very low, this study has shown that the percolation loss in Kole lands could be as high as 28.6 mm. So by maintaining water level in the canal, we can save wastage of water due to deep percolation. Shortage of irrigation water is a serious problem in most of Kole area during Punja season. Knowledge of water requirement of rice in kole lands will greatly help in efficient utilisation of the limited water available in the reservoirs.